2012
DOI: 10.1111/j.1365-2923.2012.04302.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative, emotion and action: analysing ‘most memorable’ professionalism dilemmas

Abstract: Findings extend previous research into issues related to professionalism by exploring relationships between narrative, emotion and action in the context of written narratives of most memorable dilemmas. We encourage medical educators to help students construct coherent and emotionally integrated narratives to make sense of negative professionalism dilemmas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
162
4
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 115 publications
(175 citation statements)
references
References 55 publications
(219 reference statements)
7
162
4
1
Order By: Relevance
“…The second finding suggests that students' empathy for patients related to unjustified unethical events does not decline across their education, but remains steady [2]. Indeed, across many of our studies investigating students' dilemmas, students frequently reported experiencing distress during and sometimes up to a year after these events and narrated events with a great deal of negative emotion [2,[6][7][8]11]. Having examined students' emotional reactions to their experiences of professionalism dilemmas, we now consider in greater depth students' actions in the face of their dilemmas and the reasons they give for such actions.…”
Section: Moral Distress and Its Correlatesmentioning
confidence: 99%
See 4 more Smart Citations
“…The second finding suggests that students' empathy for patients related to unjustified unethical events does not decline across their education, but remains steady [2]. Indeed, across many of our studies investigating students' dilemmas, students frequently reported experiencing distress during and sometimes up to a year after these events and narrated events with a great deal of negative emotion [2,[6][7][8]11]. Having examined students' emotional reactions to their experiences of professionalism dilemmas, we now consider in greater depth students' actions in the face of their dilemmas and the reasons they give for such actions.…”
Section: Moral Distress and Its Correlatesmentioning
confidence: 99%
“…In an examination of 680 UK medical students' written narratives of their most memorable professionalism dilemmas (both witnessing and participating in transgressions), Rees, Monrouxe, and McDonald found that 55 percent contained evidence of students' resistance to lapses, often detailing multiple acts of resistance [8].…”
Section: Professionalism Dilemmas: Acts Of Resistance and Compliancementioning
confidence: 99%
See 3 more Smart Citations